Analisis Perbandingan Anggaran dan Realisasi Pendapatan dan Belanja Pemerintah Desa di Provinsi Jawa Tengah Tahun 2022 - 2023 - Anggita Kurniawati Dewi; Diva Varella Firanika; Putri N.M Nababan; Kenni Siahaan; Regina Hanna Noisy (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study discusses a comparison between the budget and the realization of revenue and expenditure in village governments in Central Java Province for the years 2022–2023. The background of this research lies in the crucial role of village finance in supporting regional autonomy and development at the local level. The main objective is to evaluate financial management performance through the analysis of financial ratios, such as revenue growth, expenditure growth, locally generated revenue (PAD), effectiveness, efficiency, and fiscal independence. The method used is descriptive quantitative analysis based on data from the Budget Realization Report (LRA). The findings show that 2023 experienced improvements compared to 2022, as indicated by increases in revenue, expenditure, and PAD. However, effectiveness slightly declined, and efficiency showed signs of budget inefficiency. The level of village fiscal independence also increased, although it has not yet reached full autonomy. These findings indicate that although the direction of village financial management has improved, a comprehensive evaluation of budget effectiveness and efficiency is still necessary. Therefore, village governments need to strengthen their planning and financial control strategies to ensure more optimal, accountable, and sustainable fund utilization.